Association of Personal Protective Equipment with De Novo Headaches in Frontline Healthcare Workers during COVID-19 Pandemic: A Cross-Sectional Study - Zaheer, Rumeesha; Khan, Maheen; Tanveer, Ahmed; Farooq, Amal; Khurshid, Zohaib (European Journal of Dentistry, 2020)
Objectives This study aimed to determine the association of personal protective equipment (PPE) usage with new-onset headaches and exacerbation of pre-existing headache disorders among healthcare workers at the frontlines during coronavirus disease 2019 (COVID-19) pandemic.Materials and Methods A descriptive cross-sectional survey was conducted across Pakistan in June–July 2020. The study was approved by Ethical Committee, Armed Forces Institute of Dentistry, Rawalpindi (IRB form no.905/Trg-ABP 1K2). A qualitative questionnaire was developed and was shared via different social networks. The questionnaire was closed when 241 responses were received.Statistical Analysis Descriptive analysis was performed on demographic data. Chi-squared analysis was performed between demographic data and PPE-usage patterns among participants with or without de novo headaches. Univariable and multivariable logistic regression models were used to compare variables with the development of new-onset headaches. Chi-squared test was also performed between demographic data and other factors that may be causing new-onset headaches. A p-value < 0.05 was considered significant.Results A total of 241 healthcare workers participated, of which 68 participants (28.2%) reported de novo headaches since the start of the pandemic. Incidence of pre-existing headaches (odds ratio [OR] = 1.91; 95% confidence interval [CI]: 0.99–0.37; p = 0.049) was associated with new-onset headaches. Post hoc multivariable logistic regression analysis stated that incidence of pre-existing headaches (OR = 1.88; 95% CI: 0.94–3.78; p = 0.75) and age (OR = 2.21; 95% CI: 0.47–10.33; p = 0.36) was independently associated with new-onset PPE-induced headaches but was not statistically significant. Chi-squared analysis showed a statistically significant relationship between other factors (sleep deprivation, emotional stress, etc.) and department of activity, gender, and occupation (p < 0.05).Conclusion Healthcare workers with previous history of pre-existing headaches were found to be more susceptible to PPE-induced headaches during COVID-19 pandemic. However, age and the department where the healthcare workers performed may also be risk factors.
Keywords: COVID-19; de novo headaches; healthcare workers; PPE; new-onset headaches